Malawian urbanism and urban poverty: geographies of food access in Blantyre. Issue Volume 13:Issues 1(2020) (2nd January 2020) - Riley, Liam
ABSTRACT: Malawi is among the world's least urbanised countries, yet Malawian cities are growing rapidly and most growth is in unplanned informal settlements. Conventional approaches to urban planning are inadequate to address the growing problem of urban poverty. New perspectives on the nature of Malawian urbanism, built upon notions of liveable, sustainable, and "untamed" urbanisms rooted in African contexts, are needed to generate dialogue on sustainable urbanization suited to local needs, preferences, and resources. This article is based on qualitative fieldwork in Blantyre, Malawi's second largest city. It provides descriptive accounts (drawn from in-depth interviews, participative mapping, and exploration of the city's neighbourhoods) of the types of places where residents purchase and produce food. In describing these places, context-specific observations emerge about the locally specific ways that aspects of "untamed" urbanisms, such as informal markets, rural-urban linkages, and customary land allocation, reduce vulnerability to food insecurity for the urban poor.